2007
DOI: 10.1002/adma.200601808
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Electrodes with High Conductivity and Photo‐Patternability

Abstract: Electrically conductive materials capable of bending and stretching are useful for a wide range of applications such as smart clothing, [1] flexible displays, [2] stretchable circuits, [3] strain gauges, [4] implants , [5] high-deformation microelectromechanical systems (MEMS), [4] and dielectric elastomer actuators (DEAs), [6] to name a few. The necessary strain varies from minimal (< 5 %) for applications such as retinal prostheses that only require conformal contact to a surface [5] to high (> 60 %) for lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 25 publications
0
61
0
Order By: Relevance
“…The composite is then immersed into an aqueous reducing solution, causing the Pt salt to diffuse to the surface, reducing to the metal at the polymer/liquid interface. The percolation threshold is observed for 6-7% vol Pt salt at which point the surface resistance of the electrode is ∼ 200 Ω/square, and it drops down to 2.2 Ω/square for 15% vol [80]. The Young's modulus of the composite is shown to be unaffected by the quantity of filler and remains close to that of pure Loctite 3108 (10 MPa) [82].…”
Section: Photopatternable Electrodesmentioning
confidence: 68%
See 1 more Smart Citation
“…The composite is then immersed into an aqueous reducing solution, causing the Pt salt to diffuse to the surface, reducing to the metal at the polymer/liquid interface. The percolation threshold is observed for 6-7% vol Pt salt at which point the surface resistance of the electrode is ∼ 200 Ω/square, and it drops down to 2.2 Ω/square for 15% vol [80]. The Young's modulus of the composite is shown to be unaffected by the quantity of filler and remains close to that of pure Loctite 3108 (10 MPa) [82].…”
Section: Photopatternable Electrodesmentioning
confidence: 68%
“…However, intrinsically patternable compliant electrodes are very desirable, for they can greatly simplify the structuring process. Delille, Urdaneta et al have reported on photosensitive electrodes based on platinum salts mixed in a photosensitive elastomer (Loctite 3108) [80][81][82]. The ingenuity of the process resides in the use of a filler (Pt salt) which is transparent to UV light.…”
Section: Photopatternable Electrodesmentioning
confidence: 99%
“…[7,8] Metal wrinkles, thin films of metal on polymer substrates, have promise for applications in molecular detection, optical devices, filters and sorters, high-surface-area conductors and actuators, and even metrology. [9][10][11][12] We have developed a rapid approach to create metal nanowrinkles of tunable size and demonstrable utility on a shape memory polymer, [13,14] pre-stressed polystyrene (PS) sheets commercially available as the children's toy Shrinky-Dinks.…”
mentioning
confidence: 99%
“…To this end, the normalized resistance (R/R 0 , where R 0 is the initial resistance and R is the final resistance) was measured under application of an external force (R 0 is shown in Supplementary Table S2). Electrical hysteresis in the stretchable electronics is important because electrical conductance should ideally be reproducible under strain cycling to maintain a high-accuracy operation 25 . The hysteresis of the metal on the PDMS layer was measured as a function of the stretching ratio ( Fig.…”
Section: Mechanical Reliability Testmentioning
confidence: 99%
“…Several modified materials have been tested for their utility in flexible electronics, including nanoporous gold films suffused with nanometer-sized clusters of a platinum (Pt) salt 25 , aligned singlewalled carbon nanotubes (SWCNT) 26 , concentrated silver nanoparticle inks 27 , dissolvable films of silk fibroin 28 and elastic conductors comprising uniformly dispersed SWCNTs 29 . Many of these methods were developed to realize stretchable soft electronics that could accommodate large applied strains without fracturing.…”
mentioning
confidence: 99%